Some Estimates for the Cost Effectiveness of Educational Inputs for Reading Performance of Disadvantaged Children in California Title I Projects - Kiesling, Herbert J.; Rand Corp., Santa Monica, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This report presents the findings and implications of some research on the relationships of some educational inputs and reading performance of disadvantaged California Title I pupils which utilized a highly simplified model of the compensatory education process. The data for the study were gathered by questionnaire administered in personal interviews to a six percent sample of California Title I projects, enrolling ten percent of California Title I students. All projects in the study used the same performance measure, the Stanford Reading Test. Information was gathered and used for pupils in four elementary grades. The instructional variable which is most consistently and dependably related to reading gains was that for the trained reading specialist. Specialist instruction was the only school input related to reading performance in the third grade considered separately, with the strength of the relationship even stronger in that grade than in the four pooled grades. While the variables for instruction by professionals were less statistically significant, they showed signs of having some importance. Of the variables constructed to measure planning and coordination, only that for hours of planning itself was related to performance. (Author/JM)
Educational level discussed: Elementary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Compensatory Education; Cost Effectiveness; Disadvantaged Youth; Educational Resources; Elementary Education; Input Output Analysis; Multiple Regression Analysis; Paraprofessional School Personnel; Program Evaluation; Reading Consultants; Reading Programs; Resource Allocation; State Surveys; California; Elementary Secondary Education Act Title I -- Elementary Secondary Education Act Title I Program